Frameworks and tools for risk assessment of manufactured nanomaterials. (October 2016) - Hristozov, Danail; Gottardo, Stefania; Semenzin, Elena; Oomen, Agnes; Bos, Peter; Peijnenburg, Willie; van Tongeren, Martie; Nowack, Bernd; Hunt, Neil; Brunelli, Andrea; Scott-Fordsmand, Janeck J.; Tran, Lang; et al.
Abstract: Commercialization of nanotechnologies entails a regulatory requirement for understanding their environmental, health and safety (EHS) risks. Today we face challenges to assess these risks, which emerge from uncertainties around the interactions of manufactured nanomaterials (MNs) with humans and the environment. In order to reduce these uncertainties, it is necessary to generate sound scientific data on hazard and exposure by means of relevant frameworks and tools. The development of such approaches to facilitate the risk assessment (RA) of MNs has become a dynamic area of research. The aim of this paper was to review and critically analyse these approaches against a set of relevant criteria. The analysis concluded that none of the reviewed frameworks were able to fulfill all evaluation criteria. Many of the existing modelling tools are designed to provide screening-level assessments rather than to support regulatory RA and risk management. Nevertheless, there is a tendency towards developing more quantitative, higher-tier models, capable of incorporating uncertainty into their analyses. There is also a trend towards developing validated experimental protocols for material identification and hazard testing, reproducible across laboratories. These tools could enable a shift from a costly case-by-case RA of MNs towards a targeted, flexible and efficient process, based on grouping and read-across strategies and compliant with the 3R (Replacement, Reduction, Refinement) principles. In order to facilitate this process, it is important to transform the current efforts on developing databases and computational models into creating an integrated data and tools infrastructure to support the risk assessment and management of MNs. Graphical abstract: Highlights: Ongoing validation/standardisation of physicochemical characterization and toxicity protocols Ongoing development of quantitative in silico hazard tools and high-tier exposure models Need for developing nanosafety data and tools infrastructure Need for calibrating and validating modelling tools Need for developing grouping and intelligent testing strategies for nanomaterials